2013
DOI: 10.1158/1078-0432.ccr-13-0776
|View full text |Cite
|
Sign up to set email alerts
|

Dacarbazine in Solitary Fibrous Tumor: A Case Series Analysis and Preclinical Evidence vis-à-vis Temozolomide and Antiangiogenics

Abstract: Purpose: To explore the value of triazines in solitary fibrous tumor (SFT). Experimental Design: We retrospectively reviewed 8 cases of patients with SFT treated with dacarbazine (1,200 mg/m 2 every 3 weeks) as from January 2012. Then, we studied a dedifferentiated-SFT subcutaneously xenotransplanted into severe combined immunodeficient (SCID) mice. Dacarbazine, temozolomide, sunitinib, bevacizumab, and pazopanib were administered at their reported optimal doses for the mouse model when mean tumor volume (TV) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 30 publications
2
40
0
Order By: Relevance
“…The presence of the typical NAB2-STAT6 rearrangement -recently described in human SFT [12] -was confirmed in xenograft by RT-PCR [10].…”
Section: Experimental Model and Pharmacological Studiessupporting
confidence: 56%
See 3 more Smart Citations
“…The presence of the typical NAB2-STAT6 rearrangement -recently described in human SFT [12] -was confirmed in xenograft by RT-PCR [10].…”
Section: Experimental Model and Pharmacological Studiessupporting
confidence: 56%
“…SFT represents a very rare disease and very few data are available on its sensitivity to pazopanib, that is the only antiangiogenic agent approved for STS treatment. Our preclinical results showed that pazopanib is less active compared to other antiangiogenics in a high-grade dedifferentiated-SFT mouse model [10]. By contrast regorafenib was found to be the most interesting compound.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…[7][8][9][10][11][12][13][14], and 10 as having dedifferentiated solitary fibrous tumors (nos. [15][16][17][18][19][20][21][22][23][24].…”
Section: Patients and Primary Tumorsmentioning
confidence: 99%